Long-distance movements in pelagic seabirds: at-sea behaviour and life-history consequences - Fayet, A (2015)
Throughout their lives, animals have to make trade-offs between current and future events in their annual cycle. Long-lived migratory species in particular have to balance the cost of reproduction with adult overwinter survival, which is heavily dependent on migration. Behavioural plasticity, perhaps through experience and learning, may play a role in shaping individual variations in life-history decisions. The mechanisms by which such variations develop, and their potential effects on life-history traits, are poorly understood. This thesis uses two species of long-lived migratory seabirds, the Atlantic puffin Fratercula arctica and the Manx shearwater Puffinus puffinus, to address these questions, combining spatial tracking data with fine-scale measures of individual behaviour during long-distance at-sea movements. At-sea behaviour (measured with estimates of daily activity budgets) varied amongst individuals of different sex, age, and colonies. Individual variations in non-breeding behaviour were affected by investment in the previous season, and such variations had important implications for individual fitness. Puffins which visited the Mediterranean Sea foraged more and had a higher breeding success than puffins which remained locally. In addition, females puffins which foraged more during the winter, regardless of their location, laid earlier (which is associated with higher fledging success) and had a higher breeding success. Shearwaters which invested more in reproduction and started fall migration later spent less time resting at the wintering grounds than in other years, laid later and had a lower breeding success the following season. Shearwaters which invested less in reproduction showed the opposite trend. These behavioural differences were reflected in the birds' energy expenditure. Higher energy expenditure often correlated with higher fitness. Finally, pairs of puffins which followed similar migratory routes laid earlier the following year, why this was the case remained unclear. Environmental conditions were likely drivers of individual variation in at-sea behaviour. Puffins from multiple colonies across their breeding range spent more time foraging when in colder and productive waters. Furthermore, puffins from colonies at higher latitudes foraged in colder waters, despite not necessarily remaining close to their colony; this suggests a local adaptation to temperature. In shearwaters, immature individuals foraged in less productive waters than breeding adults, which resulted in a lower foraging efficiency (mass gain per unit of time spent foraging). Spatial segregation occurred between individuals of different age, sex, colonies and potentially individuals of different quality, often accompanied by differences in activity budgets. Although intra-specific competition was a likely driver of the observed segregated at-sea distributions - for example between immature and breeding shearwaters - it was unlikely to be the only factor. Spatial segregation between pair members in puffins in the months leading to the breeding season, accompanied with higher female foraging effort and breeding success, suggests that segregation resulted from different energy or nutritional requirements, perhaps related to egg laying. Overall, this thesis highlights how the investigation of the behaviours underlying long-distance movements can be a powerful tool to study drivers of breeding and non-breeding distributions and migratory routes, and the important consequences that individual variation in behaviour may have on individual fitness, and ultimately on population dynamics and the evolution of life-histories.